Pengaruh Kapabilitas Pemasaran Digital, Orientasi Pasar, dan Literasi Digital terhadap Kinerja Pemasaran UMKM - Ida Matia; Tomy Dwi Cahyono (SENTRI: Jurnal Riset Ilmiah, 2026)
Digital transformation has changed the logic of competition for micro, small, and medium enterprises (MSMEs). However, the consequences of digital adoption on performance depend on the organizational capabilities that convert technology into market outcomes. This study analyzes the influence of digital marketing capabilities, market orientation, and digital literacy on the marketing performance of SMEs in Sumbawa Regency, Indonesia. The research uses a quantitative and explanatory design with a target population of more than 1,359 SMEs registered with local agencies that handle cooperatives, industry, trade, and SMEs. Purposive sampling requires that the business has been operating for at least two years, using digital platforms for marketing for at least one year, and is represented by the owner or main manager who understands the business's marketing strategy. The analysis model uses reflective measurement and Partial Least Squares Structural Equation Modeling (PLS-SEM) thru SmartPLS 4 with 5,000 bootstrap subsamples. In this study, data from 100 respondents were used and calibrated according to the sampling design. The results show that digital marketing capability (β = 0.306; t = 5.983; p < 0.001), market orientation (β = 0.293; t = 6.031; p < 0.001), and digital literacy (β = 0.351; t = 6.846; p < 0.001) positively influence marketing performance. The model explains 54.1% of the variance in marketing performance and meets the criteria for reliability, validity, collinearity, effect size, and predictive relevance. These findings expand the resource-based and dynamic capability perspectives by demonstrating that technology-related competencies, market sensing, and human digital competencies are complementary resources for MSME performance.